How Does the Implementation of Social Entrepreneurship Business-to-Business Marketing Strategy? - Retnaningsih, Retnaningsih; Yuridis, Melani Sukma; Dewi, Febriantina (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
XYZ as a social entrepreneur in Bogor, produces handicrafts from newspapers to raise public awareness of environmental and social issues. This study aims to identify the marketing mix applied by XYZ, analyze customer perceptions of the marketing mix, and formulate recommendations for XYZ's marketing mix 4.0 to increase demand for newspaper craft products. Convenience sampling was used, and descriptive data analysis was performed. The respondents included three internal company representatives, 13 customers, and 12 prospective customers. According to the research findings, XYZ successfully implemented a 4P marketing mix strategy that covered product, price, place/distribution, and promotion. XYZ's marketing strategy in these areas has been rated highly in the excellent category of product (100%), price (85%), place/distribution (77%), and promotion (92%). However, the research also suggests that a company could enhance its marketing tactics by adopting the 4C marketing mix (co-creation, currency, communal activation, and conversation) based on insights gathered from customers and potential customers to better cater to the market's needs.